2009
DOI: 10.1097/pas.0b013e31819c6ff9
|View full text |Cite
|
Sign up to set email alerts
|

S-100A1 Is a Reliable Marker in Distinguishing Nephrogenic Adenoma From Prostatic Adenocarcinoma

Abstract: Nephrogenic adenoma is a benign lesion that may occur at any site of the genitourinary tract, usually in association with previous urothelial injuries. Although its pathogenesis is still debated, recent studies seem to confirm its derivation from renal tubular epithelium, rather than from a metaplastic process of urothelium. In addition to its uncertain origin, there can be diagnostic difficulty in distinguishing nephrogenic adenoma from prostatic adenocarcinoma, particularly with lesions arising in the prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…S100A1 was found to be differentially expressed in clear cell renal cell carcinoma and papillary renal cell carcinoma, and the differential expression may be a potentially useful marker to differentiate the chromophobe renal cell carcinoma from renal oncocytoma ( 7 , 8 ). S100A1 can also be used to differentiate other tumors ( 21 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…S100A1 was found to be differentially expressed in clear cell renal cell carcinoma and papillary renal cell carcinoma, and the differential expression may be a potentially useful marker to differentiate the chromophobe renal cell carcinoma from renal oncocytoma ( 7 , 8 ). S100A1 can also be used to differentiate other tumors ( 21 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…The reported expression of P504S in nephrogenic adenoma ranges from 58% to 100%, and most nephrogenic adenomas were also CK903 negative. 86,188,189 The similarity in certain morphologic features and the P504Sþ/CK903À immunoprofile of nephrogenic adenoma make the distinction between prostate carcinoma from nephrogenic adenoma challenging. Additional immunomarkers, especially PSA, PAX2 (or PAX8), and CK7 can help to differentiate nephrogenic adenoma from prostate carcinoma.…”
Section: Immunomarkers That Aid In the Diagnosis Of Malignancymentioning
confidence: 99%
“…46 Moreover, recent studies demonstrated a strong and distinct cytoplasmic or nucleocytoplasmic staining of S100A1 in 94% (17 of 18) of the NAs examined. 47…”
Section: Immunohistochemical Findingsmentioning
confidence: 99%